JFK, LBJ, and the Democratic Party - Savage, Sean J., 1964- (SUNY series on the presidency., 2004)
"JFK, LBJ, and the Democratic Party is a detailed, comprehensive, and provocative account of presidential party leadership in the turbulent 1960s. Using many primary sources, including resources from presidential libraries, state and national archival material, public opinion polls, and numerous interviews, Sean J. Savage reveals for the first time the influence of Presidents John F. Kennedy and Lyndon B. Johnson on the chairmanship, operations, structure, and finances of the Democratic National Committee. Savage further enriches his account with telephone conversations recently released from the Kennedy and Johnson presidential libraries, along with rare photos of JFK and LBJ."--Jacket